Menjaga Kualitas Pembelajaran Praktikum Pengolahan Data Secara Daring pada Mata Pelatihan Analisis dan Interpretasi Data - Naily Kamaliah; Alpha Fadila Juliana Rahman (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
[MAINTAINING THE QUALITY OF LEARNING DATA PROCESSING PRACTICUM IN SUBJECT OF TRAINING DATA ANALYSIS AND INTERPRETATION]. Online learning during the SARS-CoV2 virus pandemic is a necessity in order to avoid the spread of the virus. But in its implementation, it becomes a challenge, especially in practicum learning. The implementation of online training is a response to the situation and conditions in the SARS-CoV2 virus pandemic which forces classical training to migrate to online training. The purpose of this study was conducted to find out what factors support the achievement of learning objectives, in classical learning, e-learning, and whether the learning strategies that have been applied in e-learning can maintain the quality of training. The instrument in this study was an assessment of the evaluation of learning from participants for the facilitator, on 3 waves of classical PPJFP and 3 waves of PPJFP e-learning, with a total of 126 training participants as respondents. Data processing and analysis were carried out by simple regression analysis, to find out the factors that influence the achievement of learning objectives; as well as an independent sample t-test to compare classical learning methods (face to face) and e-learning. The results showed that the systematic presentation of learning materials and the ability to present the material were the spearheads in the achievement of face-to-face learning. In synchronous learning through the E-learning Platform, aspects of how the facilitator answers questions are important points in learning through e-learning; and e-learning at the syncronus stage is able to maintain the quality of learning.